Domiciliary cockroaches found in restaurants in five zones of Kuala Lumpur Federal Territory, peninsular Malaysia - Jeffery, J.; Sulaiman, Syahnaz; Oothuman, Pakeer; Razak, A; Muslimin, M; Kamil-Ali, O.B; Rohela, M; Abdul-Aziz, Noraishah Mydin; Vellayan, S; Zainol-Ariffin, P; Paramaswaran, S (Malaysian Society of Parasitology and Tropical Medicine, 2012)
The following domiciliary cockroaches were collected from restaurants in five zones of Kuala Lumpur Federal Territory, Malaysia using 1L glass beaker traps baited with ground mouse-pellets: Periplaneta americana (Linnaeus) (n = 820), Periplaneta brunnea Burmeister (n = 46), Blattella germanica (Linnaeus) (n = 12504), Supella longipalpa (Fabricius) (n = 321), Symploce pallens Stephens (n = 29) and Neostylopyga rhombifolia (Stoll) (n = 5). The following bacteria were isolated from 10 cockroach specimens: Enterobacter cloacae, Klebsiella pneumoniae ssp. pneumoniae, Klebsiella pneumoniae ssp. rhinoscleromatis and Serratia liquefaciens from 5 B. germanica; Acinetobacter calcoaceticus var. anitratus, Citrobacter diversus/amalonaticus, Escherichia vulneris and K.p. pneumoniae from 3 P. brunnea; and Citrobacter freundii, Enterobacter agglomerans 4, Escherichia adecarboxylate, E. vulneris, K. p. pneumonia, K. p. rhinoscleromatis and Proteus vulgeris from 2 P. americana.